Synthesis and establishment of physico-chemical constants 2-(5-( chinoline -2-il, 2-hydroxyquinoline-4-іл)-4-R1-1,2,4-triazole-3-ілтіо) acetate acids and their esther - Т. М. Kaplaushenko; О. І. Panasenko; Y. G. Samelyuk (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The large interest in the plan of search biologically of active agents is caused by the heterocyclic system of 1,2,4-triazole, due to high biological activity, and by the low indexes of toxicness, that inherent it to the structural analogues. Today in medical practice the derivatives of 1,2,4-triazole are used as high-efficiency antioxidants, cytostatic antimycotic agent , antidepressants and others. Literary information testify that among connections, representatives derivative of 3-tio-1,2,4-triazole range condensed with heteryl carboxylic acid, and their derivatives, find matters with the wide spectrum of biological action. The primary purpose of this work is continuation of synthetic researches 5-(chinoline-2-il, 2-hydroxyquinoline-4-il)-4-R1-1,2,4-triazole-3-tion, namely synthesis of new 2-(5-(chinolin-2-il, 2-hydroxyquinoline-4-il)-4-R1-1,2,4-triazole-3-iltio) acetate acids, their esteriv and establishment for the new structural derivatives of physical and chemical constants, confirmation of structure and individuality. On the basis of purposeful synthesis was received 10 new, connections derivatives of 1,2,4-triazole not described in literature, that contain the kernels of triazole`s cycle of chinole in a 5 position, or 2- hydroxyquinoline deputies, namely 2-(5-(chinoline-2-il, 2-hydroxyquinoline-4-il)-4-R1-2,4-dihydro-3Н-1,2,4-triazole-3-iltio) acetate acids and their esteras. For the synthesized connections by the modern physical and chemical methods of analysis their structure is well-proven, and physical and chemical constants are set. Structure of synthesized esteriv 2-(5-(quinoline-2-il, 2-hydroxyquinoline-4-il)-4-R1-1,2,4-triazole-3-iltio) of acetate acids is confirmed the complex use of element analysis and ICh-spectrophotometry.